2022
DOI: 10.1155/2022/3583985
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Expression Patterns of Immune Checkpoints Identifies New Subtypes and Emerging Therapeutic Indicators in Lung Adenocarcinoma

Abstract: Immune checkpoint genes (ICGs) play pivotal roles in tumor immune microenvironment (TIME), and thus, targeting them represents a promising strategy for cancer immunotherapy. However, the genetic landscape of ICGs in lung adenocarcinoma (LUAD) is still unknown. Herein, we comprehensively evaluated the ICG expression profiles of 1439 LUAD samples and linked ICG expression patterns with infiltration of immune cells, clinical features, and response to immune checkpoint blockade (ICB). The ICGscore was developed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 47 publications
(47 reference statements)
0
12
0
Order By: Relevance
“…Significant differential expression of ICGs was observed in tumors ( Figure 5C ), and these ICGs had a distinct cancer-specific profile compared to normal controls ( Figure 5D ). We found that the expression of most ICGs was up-regulated in KIRC, KIRP, ESCA, SKCM, and HNSC compared to para-cancerous tissues, suggesting a potential response to immunotherapy in the corresponding tumors ( Zhang et al, 2022 ).…”
Section: Resultsmentioning
confidence: 91%
“…Significant differential expression of ICGs was observed in tumors ( Figure 5C ), and these ICGs had a distinct cancer-specific profile compared to normal controls ( Figure 5D ). We found that the expression of most ICGs was up-regulated in KIRC, KIRP, ESCA, SKCM, and HNSC compared to para-cancerous tissues, suggesting a potential response to immunotherapy in the corresponding tumors ( Zhang et al, 2022 ).…”
Section: Resultsmentioning
confidence: 91%
“…A list of the top 20 enriched pathways was selected with adjusted p < 0:05. To estimate the abundance of 23 immune cell infiltrations in TNBC, the single-sample gene-set enrichment analysis (ssGSEA) algorithm was performed as described before [ 21 ]. Gene sets for each immune cell type that we used were reported, previously [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…A list of the top 20 enriched pathways was selected with adjusted P < 0:05. To estimate the abundance of 23 immune cell in ltrations in TNBC TIME, the single-sample gene-set enrichment analysis (ssGSEA) algorithm was performed as described before [21]. Gene sets for each immune cell type that we used were reported, previously [22].…”
Section: Consensus Molecular Clustering Of Irgs and Gene Set Variatio...mentioning
confidence: 99%